ANALISIS PENERAPAN ELECTRONIC ROAD PRICING PADA JALAN SUDIRMAN JAKARTA GUNA MENCIPTAKAN TRANS-PORTASI YANG BERKELANJUTAN - Nomleni, Ida Agustin (Program Studi Teknik Sipil Fakultas Teknik Universitas Atma Jaya Yogyakarta, 2019)
Jakarta is a province in Indonesia with a rapid population growth. Data obtained from the Jakarta Central Bureau of Statistics shows that Jakarta had a population of 102.776 in 2016, increasing to 103.742 in 2017. This rise in population and the role of Jakarta as the center of the economy have led to an uncontrolled increase for the need of different transportation modes. Based on the Jakarta transportation statistics (2017), the number of motorized vehicles in Jakarta reached 20.972.175 units, while the toll road built was only 7.094.000 meters. So it can be concluded that each vehicle only got 0.3382 meters of space. According to data obtained from Numbeo in 2019, Jakarta ranked 5th as the biggest contributor to congestion in Indonesia with a congestion index of 274.39. In order to overcome these problems, various efforts need to be taken, one of which is by implementing Electronic road pricing in several roads in Jakarta which is considered to be one of the solutions to reduce congestion. The purpose of this study is to analyze the potential and problems that arise in the application of Electronic road pricing on Jenderal Sudirman road, Jakarta. The research method used is a combination of literature study and survey using a questionnaire. To achieve effectiveness and efficiency of the electronic road pricing system, studies are carried out in various aspects, so that Electronic road pricing can be one of the solutions to traffic congestion in Indonesia. Based on the result of study, it can be concluded that electronic road pricing implementation can be a solution for traffic congestion especially on Jenderal Sudirman Road, Jakarta if the implementation is integrated with public transportation.